Antifungal susceptibility testing with YeastONE™ is not predictive of clinical outcomes of Cryptococcus neoformans var. grubii fungemia. (10th August 2021) - Yang, Jeng-How; Huang, Po-Yen; Cheng, Chun-Wen; Shie, Shian-Sen; Lin, Zhong-Fu; Yang, Lan-Yan; Lee, Chia-Hui; Wu, Ting-Shu
Abstract: Mortality rates due to Cryptococcus neoformans var. grubii fungemia remain significant despite treatment with antifungal drugs. The predictive function of antifungal susceptibility and its correlation with treatment outcome remains controversial. A retrospective study was conducted from January 1, 2009, to December 31, 2016, on 85 patients with C. neoformans var. grubii fungemia confirmed by matrix-assisted laser desorption ionization–time-of-flight mass spectrometry. Antifungal drug susceptibility was determined using the YeastONE™ colorimetric broth microdilution method coupled with Vizion™ System following the Clinical and Laboratory Standards Institute guidelines. Six antifungal agents—amphotericin B, fluconazole, flucytosine, itraconazole, posaconazole, and voriconazole—were tested. The patients' demographic data and clinical information were abstracted for further analyses. Antifungal regimens consisting of amphotericin B with or without fluconazole or flucytosine were administered for induction treatment of these patients, followed with intravenous or oral fluconazole for maintenance therapy. Clinical outcomes were defined by 14- and 30-day mortality rates. Risk factors associated with outcomes were fitted in a logistic regression model by univariate or multivariate method. Eighty-five patients with C. neoformans var. grubii fungemia were enrolled in the study. The Sequential Organ Failure Assessment Score, Glasgow Coma Scale, Charlson comorbidity score, and adequate duration of therapy for amphotericin B were predictors for mortality in univariate analysis. Antifungal susceptibility testing with YeastONE™ does not predict clinical outcomes of C. neoformans var. grubii fungemia. Greater disease severity, high comorbidities, poor consciousness level, and inappropriate treatment were associated with increased mortality in cryptococcemia cases. Lay Summary: Cryptococcus neoformans is an encapsulated yeast living in both plants and animals that is composed of three main serotypes: C. neoformans var. grubii, C. neoformans var. gattii, and C. neoformans var. neoformans. C. neoformans var. grubii is the most common disease-causing Cryptococcus species worldwide. C. neoformans var. gattii is more prevalent than C. neoformans var. neoformans in both tropical and subtropical regions of Asia. C. neoformans causes severe, even fatal, diseases such as pulmonary infection, bloodstream infection, skin and soft tissue infection, bone and joint infection, central nervous system infection, and disseminated infection, regardless of host immunocompetence. We conducted a retrospective study on 85 patients who contracted cryptococcemia from January 1, 2009, to December 31, 2016. This work conducted both microbiological and clinical studies involving in vitro susceptibility testing, demographic data, comorbidities, treatment modalities, and treatment outcomes. We utilized a modern medical technique-based instrument, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF MS; Biotyper, Bruker Daltonics, Inc.), which determines the unique proteomic fingerprint of an organism, to identify the C. neoformans serotype. We utilized Thermo Fisher Scientific™ Sensititre™ YeastONE™ colorimetric broth microdilution plates coupled with a Vizion™ Digital MIC Viewing System (a computer-assisted optical reading machine) to determine the in vitro susceptibility of amphotericin B, flucytosine, fluconazole, itraconazole, posaconazole, and voriconazole against 85 C. neoformans var. grubii blood isolates. In conclusion, the susceptibility patterns of these antifungal agents did not correlate significantly with treatment outcomes. However, a lower disease severity score, a lower Glasgow Coma Scale score, fewer comorbidities, and adequate amphotericin B treatment duration were predictors for treatment success in univariate analysis.